PENGEMBANGAN GOOGLE SITES UNTUK WEB PEMBELAJARAN DI SMKN 3 GARUT - Mustofa Husni Sanoval; Iman Nasrulloh; Aceng Ahmad Rodian Susila (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of information technology opens opportunities to enhance learning quality through web-based media. This study aims to develop Google Sites-based learning media at SMKN 3 Garut using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research stages include needs analysis, design, development, implementation, and evaluation of the learning media. The results show that the developed Google Sites-based learning media achieved a very high feasibility level. Evaluation by media experts scored 94% in the